Physeal-Specific MRI Analysis of Growth Plate Disturbance Following All-Inside Anterior Cruciate Ligament Reconstruction in Skeletally Immature Patients: Does a Physeal-Sparing Technique Offer any Advantage? - Nawabi, Danyal H. (Orthop J Sports Med, 2013)
OBJECTIVES: The decision to perform anterior cruciate ligament (ACL) reconstruction in skeletally immature patients carries a risk of growth disturbance due to iatrogenic physeal injury. Multiple physeal-sparing techniques have been described but none, to our knowledge combine the benefits of an anatomic reconstruction and socket fixation, without violation of either the femoral or tibial physis at any stage of the procedure. The purpose of this study was to compare the incidence and calculate the area of post-operative physeal disturbances, using a physeal-sensitive magnetic resonance imaging (MRI) sequence*, between all-epiphyseal (AE) and partial transphyseal (PTP) ACL reconstructions in a cohort of skeletally-immature patients. METHODS: Twenty-one skeletally immature patients with a mean chronologic age of 12.7 years (range 10 to 16) undergoing all-inside ACL reconstruction were prospectively followed. Fourteen patients had an all-epiphyseal (AE) ACL reconstruction and 7 patients had a partial transphyseal (PTP) ACL reconstruction, which spared the femoral physis but crossed the tibial physis. Hamstring autograft was used in all cases. At a mean of 11.6 months follow-up, all patients were assessed for focal physeal disturbance and graft survival using a three-dimensional (3D) fat suppressed spoiled gradient-recalled echo (SPGR) MRI sequence. Angular deformity and leg length discrepancy were evaluated on full-length standing radiographs. The International Knee Documentation Committee (IKDC) subjective score and Lysholm knee score were also documented. RESULTS: The tibial physis was violated in 13/14 patients in the AE group and all patients in the PTP group. The mean area of post-operative tibial physeal disturbance (± SD) was 42.4 ± 38.6 mm(2) (mean 1.7% of total physeal area) in the AE group compared to 216.7 ± 129.1 mm(2) (mean 7.3% of total physeal area) in the PTP group (p = 0.003). The femoral physis was violated in one case in both groups resulting in a mean physeal disturbance of 1.5% of the total distal femoral physeal area. No cases of fracture, articular surface violation or avascular necrosis were noted on MRI in either group. Short-term graft survival was 100% amongst the entire cohort. There were no cases of angular deformity in either group with a mean side-side difference in the lateral distal femoral angle of 1.11° ± 1.02° in the AE group and 0.72° ± 0.65° in the PTP group (p = 0.23). No significant leg-length discrepancies were measured in either group. The mean IKDC and Lysholm scores (± SD) were 93.3 ± 5.9 and 97.8 ± 3.8 respectively in the AE group and 87.7 ± 3.5 and 96 ± 5.2 respectively in the PTP group. CONCLUSION: All-epiphyseal ACL reconstruction caused significantly less focal physeal disturbance than PTP ACL reconstruction, as determined by a 3D physeal-sensitive MRI sequence. Neither technique however resulted in angular deformity or leg-length discrepancy at early follow-up. Both all-inside ACL reconstruction techniques used in this study are safe and effective at early follow-up in skeletally immature patients. Further longitudinal study of this cohort is required to determine any potential advantages of a purely physeal-sparing technique.